1982
DOI: 10.1017/s0043174500041412
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Different 2,4-D, Bentazon, Diclofop, or Diclofop-Methyl Combinations in Oat (Avena sativa) and Soybean (Glycine max)

Abstract: Oat (Avena sativaL. ‘Elgin′) and soybean (Glycine maxL. ‘Evans′) were treated with14C-diclofop-methyl {methyl ester of 2-[4-(2,4-dichlorophenoxy)phenoxy] propionic acid]} or14C-diclofop alone or in combination with 2,4-D [(2,4-dichlorophenoxy)acetic acid] or bentazon [3-isopropyl-1H-2,1,3-benzothiadiazin-4(3H)-one 2,2-dioxide] and14C-2,4-D alone or in combination with diclofop-methyl or diclofop. More radioactivity was recovered in the treatment zone after14C-diclofop-methyl applications, alone or in combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The rate of uptake was slower in sensitive field bean than in wild oat (Avena fatua L.) (Holloway and Edgerton 1992). In contrast, tolerant oat (Avena sativa L.) had faster uptake than sensitive soybean but levels were equal by 24 h after application (Hall et al 1982). Similar uptake levels were observed between tomato (Solanum lycopersicum Mill.)…”
Section: Uptake and Translocationmentioning
confidence: 58%
“…The rate of uptake was slower in sensitive field bean than in wild oat (Avena fatua L.) (Holloway and Edgerton 1992). In contrast, tolerant oat (Avena sativa L.) had faster uptake than sensitive soybean but levels were equal by 24 h after application (Hall et al 1982). Similar uptake levels were observed between tomato (Solanum lycopersicum Mill.)…”
Section: Uptake and Translocationmentioning
confidence: 58%
“…Olson and Nalewaja (1982) studied the effect of MCPA on 14 C‐diclofop methyl uptake and translocation and found that the antagonistic effect of MCPA reduced diclofop‐methyl uptake, de‐esterification, and translocation. However, there are other studies that showed no antagonism between these two herbicides (Hall et al . 1982; Kelly & Chapman 1995).…”
Section: Introductionmentioning
confidence: 93%
“…Olson and Nalewaja (1982) studied the effect of MCPA on 14 C-diclofop methyl uptake and translocation and found that the antagonistic effect of MCPA reduced diclofopmethyl uptake, de-esterification, and translocation. However, there are other studies that showed no antagonism between these two herbicides (Hall et al 1982;Kelly & Chapman 1995). Liebel and Worsham (1987) also showed that chlorsulfuron did not have any antagonistic effect on the uptake, translocation, and metabolism of diclofop-methyl.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports that the chlorophenoxy herbicides 2,4-D and MCPA cause decreased uptake, de-esterification and/or translocation of diclofop-methyl and it has been proposed that one or a combination of these effects is the cause of antagonism (Qureshi & Vanden Born, 1979;Olson & Nalewaja, 1982). However, there are also reports that these processes are unaffected by chlorophenoxy herbicides (Hall, Edgington & Switzer. 1982b;Hill, Todd & Stobbe, 1980;Kafiz et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that chlorophenoxyherbicides such as 2,4-D and MCPA and the benzoic herbicide dicamba cause antagonism of diclofop-methyl activity due to their auxin-like properties (Shimabukuro etal., 1978;Hall et al, 1982b;Shimabukuro, Hoerauf & Walsh, 1986;Fitzsimons, Barnwell & Cobb, 1988). There is good evidence that auxin-induced growth is in part mediated through H* efflux into cell walls (Taiz, 1984).…”
Section: Introductionmentioning
confidence: 99%